Pola Asuh Orangtua Berhubungan dengan Perkembangan Bicara dan Bahasa Balita di Puskesmas Ambarawa: Parenting Patterns are Associated with the Development of Toddlers' Speech and Language at the Ambarawa Community Health Center - Melania Rosaria Moniz; Isfaizah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2023)
Parenting is the way parents direct children, how they educate and teach children everything. The development of speech and language in children is greatly influenced by a healthy relationship between parents and children. The occurrence of speech and language delays in children causes children to be difficult to socialize with peers and the surrounding environment. This study aims to determine the relationship between parenting style and speech and language development in toddlers in the Working Area of the Ambarawa Health Center, Semarang Regency. The design of this study is correlational analytic with a crosssectional design. The population of this study was all toddlers of the Ambarawa Health Center, Semarang Regency as many as 717 toddlers and a sample of 88 people using the purposive sampling method. Data collection tools using Parenting Styles and Dimensions Questionnaire-Short Version (PSDQ) and KPSP. Data analysis used uni-variate analysis with frequency distribution and bi-variate analysis with Chi-square. Parents of toddlers mostly have permissive parenting (39.8%) and normal speech and language development (62.5%). There is a significant relationship between parenting style and speech and language development in toddlers in the Working Area of Puskesmas Ambarawa Semarang Regency (p value <0.001). Permissive parenting has more potential for children experiencing speech and language delays. Parents must be able to invite more children to communicate and speak in daily activities so that their development is optimal. ABSTRAK Pola asuh orang tua merupakan cara orang tua mengarahkan anak, bagaimana mereka mendidik dan mengajarkan pada anak segala hal. Perkembangan bicara dan bahasa pada anak sangat dipengaruhi adanya hubungan yang sehat antara orang tua dengan anak. Terjadinya keterlambatan bicara dan berbahasa pada anak mengakibatkan anak menjadi sulit bersosialisasi dengan teman sebaya maupun lingkungan sekitar. Penelitian ini bertujuan untuk mengetahui hubungan pola asuh dengan perkembangan bicara dan bahasa pada balita di Wilayah Kerja Puskesmas Ambarawa Kabupaten Semarang. Desain penelitian ini analitik korelasional dengan pendekatan crosssectional. Populasi penelitian ini seluruh balita Puskesmas Ambarawa Kabupaten Semarang sebanyak 717 balita dan sampel sebanyak 88 orang dengan metode purposive sampling. Alat pengambilan data menggunakan Parenting Styles and Dimensions Questionnaire-Short Version (PSDQ) dan KPSP. Analisis data menggunakan analisis univariat dengan distribusi frekuensi dan analisa bivariat dengan Chi-square. Orang tua balita sebagian besar mempunyai pola asuh permisif (39,8%) dan perkembangan bicara dan bahasa normal (62,5%). Ada hubungan yang signifikan antara pola asuh orang tua dengan perkembangan bicara dan Bahasa pada Balita di Wilayah Kerja Puskesmas Ambarawa Kabupaten Semarang (p value <0,001). Pola asuh permisif berpotensi lebih untuk anak mengalami keterlambatan bicara dan bahasa. Orang tua harus bisa lebih banyak mengajak anak berkomunikasi dan berbahasa dalam kegiatan sehari-hari agar perkembangannya optimal.